Nutritional Assessment and Management in Paediatric Chronic Kidney Disease - Jumanah Ziyad Azzouz; Osama Yousef Safdar; Farah Idriss Awaleh; Alya Abdullah Khoja; Ali Alawi Alattas; Abdulkarim Abbas Jawhari (Journal of Nutrition and Metabolism)
Nutrition in paediatrics has always been one of the most important factors for optimal growth. Children with chronic kidney disease (CKD) need special consideration for better long-term outcomes, including nutritional status, optimal height, and cognitive function. Nonetheless, there are many obstacles to overcome to attain optimal linear growth and nutritional status in children with CKD. This review highlights the need for tools to assess the growth parameters in CKD. In addition, recommendations for dietary intake play a major role in controlling electrolyte disturbances in patients with CKD. For example, it is still unclear whether it is better to restrict phosphate sources in inorganic, organic, or food additives. The review also summarises different factors such as fluid intake, route of feeding, and essential nutrients that require particular attention in paediatric patients with CKD. In summary, a multidisciplinary team is needed to devise individual nutritional plans to achieve the best outcome and improve the quality of life of patients.